(untitled) (Urdimento - Revista de Estudos em Artes Cênicas, 2018)
The author presents the two arms of his pedagogical practice. The first one is the work method Vellinho has developed – as a director, puppeteer and actor – to train professionals to the practice of the Animation Theater. His technical procedures have been improved throughout the 18 years of his company, by means of experimentations that approach the Animation Theater to other languages, as Cinema, Dance and Cartoon. The second arm is Vellinho’s work since 2008 as a professor at the university. The director was responsible for the creation of the Animation Theater discipline at UNIRIO, considering the challenges of public education’s reality in Brazil, both at University – field for the students’ professional qualification – and at Elementary, Middle and High School – the largest work field for the future teachers. His work seeks to establish real and strong links between the artist and the animated object. In this process, the crafting of the puppets is a special highlight, because that is where begins the comprehension of the puppet in its scenic expression’s entirety, a methodology Vellinho considers as a gestation